Implementation Disciplinary Character Education: A Comparative Study of Indonesian and Danish Elementary Schools - Darojati, Nuriyah Lutfi; Hidayat, Muhamad Taufik (Universitas Muhammadiyah Surakarta, 2023)
Purpose: The research aims to reveal and compare the implementation of disciplinary character education in elementary schools between Indonesia and Denmark. Methodology: This study employs a qualitative approach, utilising a literature review research method, specifically employing a comparative literature review design. The data corpus consists primarily of journal articles sourced online, supplemented by website articles and pertinent videos. To ensure data validity, several techniques are employed, including the check and recheck method, researcher validity protocols, and source triangulation. Data analysis encompasses the systematic reduction, presentation, and conclusive interpretation of gathered information. Results: The research findings illustrate similarities and disparities in implementing disciplinary character education between Indonesia and Denmark. Shared practices include the ritual of queuing before class, recognition through praise for diligent efforts, and the emphasis on timely submission of assignments. Conversely, divergences emerge in the methodologies employed. In Indonesia, disciplinary character education is primarily imparted through direct habituation in daily routines, such as students engaging in prayer before commencing lessons. In contrast, Denmark adopts a model based on exemplification, where teachers serve as role models, and students emulate disciplined behaviour accordingly. Furthermore, while Indonesian students receive instruction on adhering to traffic regulations at pedestrian crossings within classroom settings, Danish counterparts undergo repetitive teaching sessions on traffic rules, subsequently applying acquired knowledge under the supervision of their educators on the actual road. Applications/Originality/Value: The novelty of this research lies in its exploration of the implementation of disciplinary character education within elementary school settings, particularly focusing on a comparative analysis between Indonesia and Denmark.